Future Studies & Fashion: a conceptual approach (ModaPalavra e-periódico, 2013)
The prospect of signals issued by the society is a study guide that allows cross and behavioral recommendations for all levels of the market, supported by the phenomenon of emotional tendencies and synthesized into images, concepts, attitudes, movements. Studying future conditions is a strategic challenge for the actors’ social, economic, institutional and government. The objectives were: (a) present the different classifications and approac hes about the future studies found in the literature; (b) order the historical direction of the topic, pointing periods of interest and known researchers approaches discussed in reference; (c) focus on the study of prospective and its application in design of fashion products, bringing up questions about the area and contemporary future. Therewith, we sought to provide tools that assist in monitoring and enforcement trends to guide organizations in establishing an ongoing process of research and innovation.
Keywords: studies of the future; fashion; products